Strengthening Student Character Through Learning Value-Based Civic Education - Devra, Desi Devrika (UNIVERSITAS PAKUAN, 2020)
This study aims to explain the role of civic education in efforts to strengthen student character through value-based civic education methods. Civic education in higher education includes training students as future intellectuals of the country so that they can become good citizens, able to understand the philosophical values of their country, strong character, broad-minded, and democratic. This research uses a qualitative descriptive library survey method, the data sources used are from relevant journals, books and previous research. The findings of this study are that citizen education as one of the methods of character education not only introduces values to students, but also can adjust values based on Pancasila to be used as a burden of consciousness so that they can appreciate their behavior as citizens, these values will make internal stability and behavior appear when there is a meeting between opposing values